The politics of English : South Asia, Southeast Asia and the Asia Pacific - Wee, Lionel, 1963-; Goh, Robbie B. H., 1964-; Lim, Lisa (Studies in world language problems ;, 2013)
This volume brings together contributions that explore the increasingly important roles that English plays in Asia, including its contribution to economic growth, national imaginaries and creative writing. These are issues that are political in a broad sense, but the diversity of Asian contexts also means that the social, political and cultural ramifications of the spread of English into Asia will have to be understood in relation to the challenges facing specific societies. The chapters in the book collectively illustrate this diversity by focusing on countries from South Asia, Southeast Asia and the Asia Pacific. Each country has two contributions devoted to it: one paper provides an overview of the country's language policy and its positioning of English, and another provides a critical discussion of creative expressions involving the use of English. Taken together, the papers in the volume detail the most recent developments concerning the politics of English in Asia.